MAPPING THE GLOBAL RESEARCH ON COMPETITIVENESS AND INTERNATIONALIZATION FOR SMALL AND MEDIUM ENTERPRISES - Tantriana, Deasy; Murwani, F. Danardana; Muchlish, Imam (Yayasan Education and Social Center, 2024)
Develop a concept that enables proprietors of small and medium-sized enterprises (SMEs) to enter international markets more environmentally consciously, building upon the author's blueprint. A systematic literature review (SLR) investigates the complexity associated with the Internationalization of SMEs. The author complies with the following procedure: retrieve metadata from the top 35 papers tagged with the keywords internationalization, competitive advantage, and SMEs in Scopus (April 2024), sort the articles by citation count, and select reviews and SMEs as the focus of the discussion. Key players and determinants of competitive advantage for the Internationalization of SMEs are subsequently identified through bibliometric visualization and qualitative data analysis software (Biblioshiny, R Studio). The findings uncover the primary theories of Internationalization, prominent authors, reviews, and sources, and supplement Werner's determinant with several illustrative tables and graphs. The findings mentioned above demonstrate the growing significance of theories concerning competitive progress. Much work remains to be done regarding the Internationalization of small and medium-sized enterprises (SMEs), specifically about the factors contributing to a company's success in foreign markets and its establishment in the domestic market. For the future successful Internationalization of SMEs, a contribution to science is an update on pertinent topics and the identification of specific trends and gaps, including inter-theoretical integration, discourse variables, strategic fit versus opportunism, network theories concerning niche marketing, born-glocal strategies, and disruptive technologies